Glucose Control in Post-hemolytic-Uremic Syndrome Diabetes: A New Approach Offered by Sensor-Augmented Pump Therapy - Grancini, Valeria; Vianello, Federica Alessandra; Colosimo, Santo; Gaglio, Alessia; Resi, Veronica; Arosio, Maura; Ardissino, Gianluigi; Montini, Giovanni; Orsi, Emanuela (Frontiers in Pediatrics, 2022)
We report the case of a 3 years old female admitted to her town emergency department for fever (39°C) associated with diarrhoea, generalized oedema, oliguria and drowsiness. Blood test revealed metabolic acidosis, leucocytosis, increased inflammatory markers, anaemia, thrombocytopenia and acute kidney failure. Based on the diagnosis of haemolytic-uremic syndrome the patient was referred to a third level children hospital. Assisted ventilation, haemodialysis and parenteral nutrition were instituted. Blood glucose levels increased above 200 mg/dl with peaks at 500 mg/dl. Islet auto-antibodies were negative and C-peptide was undetectable, thus ruling out the diagnosis of type 1 diabetes. Multiple daily injections insulin therapy was then instituted with the following regimen: Detemir 2 U once daily and Aspart 0.5 U if blood glucose >200 mg/dl. Despite the very low insulin dosage, the patient experienced frequent and severe hypoglycaemic events during the following 24 hours and was therefore switched to sensor-augmented pump therapy. Optimal glucose control was achieved without further hypoglycaemic episodes. Moreover, thanks to the possibility to customize insulin therapy hour by hour during the day and the use of a pre-low glucose suspend system, glucose control was maintained even despite the continuous modifications in the nutritional scheme, due to the multiple complications that arose during hospitalization. This rare case of post-haemolytic-uremic syndrome diabetes, treated with sensor-augmented therapy from its outbreak, suggest for the first time the potential of this therapeutic strategy in achieving glucose control without significant hypoglycaemic episodes in children with secondary forms of diabetes associated with very low insulin requirement.